Integrated analysis of miRNAs and mRNAs in thousands of single cells - Jia Li; Jing Tian; Tao Cai (Scientific Reports)
Abstract The simultaneous sequencing of multiple types of biomolecules can facilitate understanding various forms of regulation occurring in cells. Cosequencing of miRNA and mRNA at single-cell resolution is challenging, and to date, only a few such studies (examining a quite limited number of cells) have been reported. Here, we developed a parallel single-cell small RNA and mRNA coprofiling method (PSCSR-seq V2) that enables miRNA and mRNA coexpression analysis in many cells. The PSCSR-seq V2 method is highly sensitive for miRNA analysis, and it also provides rich mRNA information about the examined cells at the same time. We employed PSCSR-seq V2 to profile miRNA and mRNA in 2310 cultured cells, and detected an average of 181 miRNA species and 7354 mRNA species per cell. An integrated analysis of miRNA and mRNA profiles linked miRNA functions with the negative regulation of tumor suppressor and reprogramming of cellular metabolism. We coprofiled miRNA and mRNA in 9403 lung cells and generated a coexpression atlas for known cell populations in mouse lungs, and detected conserved expression patterns of miRNAs among lineage-related cells. Based on this information, we identified informative age-associated miRNAs in mouse and human lung cells including miR-29, which can be understood as a conserved marker for immunosenescence. PSCSR-seq V2 offers unique functionality to users conducting functional studies of miRNAs in clinical and basic biological research.